Aspects of the biology and ecology of the South African abalone Haliotis midae Linnaeus, 1758 (Mollusca Gastropoda) along the eastern Cape and Ciskei coast - Wood, A D (Aidan David) (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1993)
The South African abalone Haliotis midae Linnaeus, 1758, is an important commercial, recreational and aquaculture mollusc species. It is the largest of the six haliotid species found in South African waters and has the second largest distributional range aside from Haliotis spadicea which is widely exploited by rock and surf anglers as bait. Analysis of population structure at Great Fish Point revealed that H. midae exhibited a high degree of microhabitat specificity, and that while dietary habits played a role in habitat selection, it was ultimately the activities of predators which confined size classes to particular niches and restricted all animals to nocturnal activities. Large (> 100 mm SL) exposed animals relied on shell thickness and adhesion to combat predators, while small (> 45 mm SL) sub-boulder animals and medium sized (50 - 95 mm SL) animals relied on their cryptic microhabitats and the protective spine canopies of co-resident urchins (Parechinus angulosus) for daytime protection. Populations of H. midae were discontinuously distributed along the coast, occupying small isolated reefs which offered a suitable array of microhabitats and a good food supply. They mostly inhabited shallow intertidal and subtidal reefs, but were occasionally encountered on deeper subtidal reefs at 4 - 5 meters. Mean length- and width-at-age were determined from growth rings composed of alternate conchiolin (dark) and aragonite (white) bands in the internal nacreous shell layer. Growth was described by the Special Von Bertalanffy growth equation: Lt(mm) = 176.998918 (1 - eâ »Â°Â·Â²â ´Â²â ´Â¹â ¹â ½t â º Â°Â·â ´â ¹â µâ ´â ¹â ´â ¾) Wt(mm) = 159.705689 (1 - eâ »Â°Â·Â¹â ¹â µâ ´Â³â ¹â ½t â º Â°Â·Â²Â¹Â¹â ¶â ¾) The ageing technique used was validated for animals from Great Fish Point and Mgwalana using independent tag-return data. The same data provided evidence that growth rates varied between animals from Great Fish Point and Bird Island. The growth data also showed that H. midae exhibited a high degree of individual variation in growth rate. Males and females exhibited similar growth rates. Exposed large animals showed a preference for red seaweeds, in particular Plocamium corallorhiza and Hypnea spicifera, while small sub-boulder cryptic animals included larger proportions of brown (Ralfsia expansa) and green (VIva spp.) algae in their diets. Exposed individuals also exhibited a higher degree of selectivity towards prey items, but in general, stomach contents reflected the most abundant seaweed types. Both drift and attached algal species were utilized by H. midae which was a nocturnal feeder. Pigments from red algae were incorporated into the shell layers giving the shells a pink or brick red colour. Haliotis midae is a dioecious broadcast spawner. Gonad Bulk Indices in combination with detailed histological examination of gonads showed that individuals were iteroparous, asynchronous spawners and that the breeding season extended from March through to October, although the peak spawning activity was between April and June. Males and females can spawn partially, totally or not at all, with atresia of residual gametes occurring after spawning. There is no resting stage, and gametogenesis is initiated directly after spawning. The structure of the ovary and testis and the process of gametogenesis is typical of haliotid species. AI: 1 sex ratio was observed from all populations studied. Sexual maturity was first attained in the 40 - 59 mm SL size class, although evidence for the smallest size at first spawning was recorded at 54.6 mm SL for females and 69 mm SL for males. Sizes at 50% sexual maturity were 72.5 mm SL (52.8 mm SW) at Great Fish Point, 72.5 mm SL (57.4 mm SW) at Mgwalana, 73.7 mm SL (51.2 mm SW) at Cape Recife, and 73.5 mm SL (53.8 mm SW) at Kelly's Beach. Haliotis midae was typically highly fecund, although a high degree of variation resulting in poor relationships between fecundity/shell length and gonad weight/shell length. The relationship between fecundity and gonad weight was linear. In the Eastern Cape, H. midae possessed a faster growth rate, smaller size at sexual maturity, smaller maximum size and lower longevity when compared to con specifics in Western Cape waters. A smaller minimum legal size of 93 mm SW is proposed for Eastern Cape animals and it is suggested that the closed season be moved to the peak spawning period between April and June. The benefit of a closed season during the spawning period is questioned, and the feasibility of closed areas as a management option for H. midae in the Eastern Cape is discussed.
Keywords: Abalones -- South Africa; Abalones -- Ecology; Abalones -- Physiology